Forecasting Flood Vulnerability in Pontianak using Multiple Linear Regression and Geospatial Information Systems (GIS) - Farhan, Firda Islamaya; Adi, Ahmad Cahyono (Department of Informatics, Siliwangi University, Indonesia, 2023)
Flood disasters frequently happen in locations with specific geographic characteristics, such as close proximity to rivers and excessive rainfall, especially during the rainy season, making most soil types contain clay and unsuitable for water absorption. One of the Indonesian cities that experiences frequent flooding is Pontianak City. Based on the parameters established in the preceding circumstances, multiple linear regression methods are used to forecast and anticipate the degree of flood risk in Pontianak City. The Quantum GIS application creates a digital map that displays the score attained in each sub-district. This is done to identify the flood-prone locations in Pontianak City and make the mitigation activities more focused and effective.